МЕДИАОБРАЗОВАТЕЛЬНЫЕ РЕСУРСЫ И ТЕХНОЛОГИИ В ПОДГОТОВКЕ СПЕЦИАЛИСТОВ БИБЛИОТЕЧНО-ИНФОРМАЦИОННОЙ СФЕРЫ (Библиосфера, 2010)
The author formulates the notion and tasks of media education and characterizes main directions of forming media competences at graduates of Institute of information and library technologies of the Kemerovo state university of culture and arts. The importance of scientific understanding of problems of media education in modern society is underlined.